Interest in Entrepreneurship: The Role of Entrepreneurial Motivation as a Mediating Variable to Student of ITB ASIA Malang - Ummi Saadah; Cipto Wardoyo; Madziatul Churiyah (Profesional Muda Cendekia Publishing, 2021)
This research gives benefit to enhance knowledge in terms of business and management education, especially for students of ITB ASIA Malang. For the students, this research can become an evaluation material to understand the effects of students’ competence, struggle, desire, and interest in entrepreneurship in entrepreneurial spirit. Incubation program available in ITB ASIA can also motivate the students to have the will to build a business and in the mentioned program can raise successful entrepreneur in any field. The population of the study of this research is the students of Faculty of Economics of ITB ASIA Malang who has taken Entrepreneurship course in a total of 226 people. Based on the research findings, it can be concluded as follow. There is a direct effect of entrepreneurship education on interest in entrepreneurship by 6.571 with the probability magnitude (Sig.) for entrepreneurship education of 0.000 < 0.05 and the value of t-count ≥ t-table (6.571 > 1.65573). There is a direct impact on gender to interest in entrepreneurship by 2.945 with the probability magnitude (Sig.) for entrepreneurship education of 0.004 < 0.05 and the value of t-count ≥ t-table (2.945 > 1.65573). There is a direct effect of entrepreneurship education on entrepreneurial motivation by 11.580 with the probability magnitude (Sig.) for entrepreneurship education of 0.000 > 0.05 and the value of t-count ≥ t-table (11.580 < 1.65573). There is a direct impact on gender to entrepreneurial motivation by 1.039 with the probability magnitude (Sig.) for gender of 0.301 < 0.05 and the value of t-count ≥ t-table (1.039 > 1.65573). There is a direct effect of interest in entrepreneurship on entrepreneurial motivation by 8.172 with the probability magnitude (Sig.) for interest in entrepreneurship of 0.000 > 0.05 and the value of tcount ≥ ttable (8.172 < 1.65573). There is a direct effect of entrepreneurship education on entrepreneurial motivation by 4.848 with a path coefficient of E2 0.394 and E1 0.716. There is a direct impact on gender to entrepreneurial motivation by 0.251 with a path coefficient of E2 0.394 and E1 0.716.